الزكاة كآلية لدعم العمالة غير الرسمية: Zakat as a mechanism to support informal employment - قوميدي تقي الدين; يونس شعيب (Journal of North African Economies, 2025)
This study aims to demonstrate the role of zakat, being a religious obligation and one of the tools of the Islamic economy, in improving the working conditions of informal sector workers, considering the work element as one of the basic elements of the production process by helping informal workers overcome their main problems of lack of income and lack of professional competence. And the absence of social protection through the programs of various zakat institutions to improve and increase incomes and wages, and their financing of vocational training programs and improving skills, in addition to providing social protection through their payment of social security contributions, in many developing countries in order to achieve decent work, which is the first step to integration. In the formal economy and to achieve sustainable development goals.